Regularity for an elliptic problem - Taqi, Ismaiel; Castro, Alfonso (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In the present paper, regularity results for linear elliptic equations are presented, where a coefficient has critical growth.